1968
DOI: 10.1113/jphysiol.1968.sp008429
|View full text |Cite
|
Sign up to set email alerts
|

Observation of changes in volume of a congested limb as a means of studying the behaviour of capacity vessels

Abstract: SUMMARY1. Experiments have been performed to determine whether the volume of a forearm congested by a cuff inflated to a low pressure (15-30 mm Hg) reflects active changes in the vascular capacity of the part while remaining relatively insensitive to the passive effects of changes in perfusion.2. Conditions were chosen in which existing evidence suggests that blood flow and capacity vary independently of each other.3. The results of these experiments suggested that active changes in capacity can be studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Continuous estimates of volume changes have been determined during inflation of a proximal limb cuff to a constant pressure (e.g. 4 kPa) (Ardill et al 1968;Abboud et al 1968).…”
Section: Measurement Of Volume Changes In a Limbmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous estimates of volume changes have been determined during inflation of a proximal limb cuff to a constant pressure (e.g. 4 kPa) (Ardill et al 1968;Abboud et al 1968).…”
Section: Measurement Of Volume Changes In a Limbmentioning
confidence: 99%
“…The maximum volume shift in response to suction with 9 kPa is about 10 ml/kg body weight (Brown et al 1966). Most authors have reported an increase in limb venous tone in response both to leg suction (Gilbert and Stevens 1966;Boreus and Hollenberg 1972;Paessler et al 1968;Page et al 1955) and lower body negative pressure (Gilbert and Stevens 1966;Ardill et al 1968;Tripathi et al 1984). However, responses were frequently small and transient (Samueloff et al 1966;Paessler et al 1968), and Epstein et al (1968) noted that the response frequently preceded the stimulus, suggesting the existence of a psychogenic component.…”
Section: Responses To Shifts In Blood Volumementioning
confidence: 99%